Food insecurity indicators of 14 OECD countries in a health economics aspect: A comparative analysis - Yılmaz, Salim; Günal, Ahmet Murat (Frontiers in Public Health, 2023)
Food insecurity refers to a lack of access to enough food to support a healthy and active lifestyle. Several reasons cause this, and its effects are wide-reaching, with potential negative impacts on health, education, and overall well-being. Addressing food insecurity requires a multifaceted approach involving governments, organizations, and individuals working together to ensure access to a balanced and nutritious diet for all. In this study, we aim to shed light on macro-level models by considering the gaps in the literature on food insecurity in international comparisons. We evaluate food insecurity risk in six criteria in terms of health expenditure, GDP per capita, and GDP growth rate. We developed a modeling approach in three stages and compared food insecurity risk among 14 OECD countries, then discussed the reasons for the rankings of the countries based on the model results. According to our findings, the United States has the lowest food insecurity risk, while Colombia has the highest. In future work, using this and similar models to link economic outcomes with important health components such as nutrition and physical activity will provide a foundation for policy development.